A novel energy consumption model for autonomous mobile robot - Gurgoze, Gurkan; Turkoglu, Ibrahim (Tubitak Scientific & Technological Research Council Turkey, 2022)
In this study, a novel predictive energy consumption model has been developed to facilitate the development of tasks based on efficient energy consumption strategies in mobile robot systems. For the proposed energy consumption model, an advanced mathematical system model that takes into account all parameters during the motion of the mobile robot is created. The parameters of inclination, load, dynamic friction, wheel slip and speed-torque saturation limit, which are often neglected in existing models, are especially used in our model. Thus, the effects of unexpected disruptors on energy consumption in the real world environment are also taken into account. As a result, a prediction success rate of 98.56% was achieved. It has also been compared with existing energy models. It was found to give 2%-6% better results than existing energy models. Finally, the effects of the parameters used in the proposed model on energy consumption were revealed in an 8-state simulation study. These dynamics have been found to have significant effects on energy consumption
Keywords: Energy model; energy consumption; mobile robot system model; slope; wheeled slip